Temperature Effect on Exploitation and Interference Competition among Microcystis aeruginosa, Planktothrix agardhii and, Cyclotella meneghiniana - Andreia Maria da Anunciação Gomes; Sandra Maria Feliciano de Oliveira e Azevedo; Miquel Lürling (The Scientific World Journal)
We studied the effect of temperature (18 and 30°C) on growth and on the exploitation and interference competition of three species: Microcystis aeruginosa (MIJAC), Planktothrix agardhii (PAT), and Cyclotella meneghiniana (CCAP). Coculturing the organisms in batch systems allowed for the examination of both competitive interactions, while the interference competition was studied in cross-cultures. The experiments were done during 10–12 days, and samples were taken for chlorophyll-a analysis, using PHYTO-PAM. The temperature did not influence exploitation competition between MIJAC and other competitors and it was the best competitor in both temperatures. PAT presented higher growth rates than CCAP in competition at 18 and 30°C. The temperature influenced the interference competition. The growth of MIJAC was favored in strains exudates at 30°C, while CCAP was favored at 18°C, revealing that the optimum growth temperature was important to establish the competitive superiority. Therefore, we can propose two hypotheses: (i) different temperatures may results in production of distinct compounds that influence the competition among phytoplankton species and (ii) the target species may have different vulnerability to these compounds depending on the temperature. At last, we suggest that both the sensitivity and the physiological status of competing species can determine their lasting coexistence.